Cutthroats - Johnstone, William W; Johnstone, J. A. (Johnstone, William W. Slash and Pecos westerns., 2019)
Lifetime outlaws Jimmy "Slash" Braddock and Melvin "Pecos Kid" Baker are ready to call it quits, but when members of their gang rebel, they must pull one last job to finance a retirement far away from the long arm of the law.